2017
DOI: 10.1002/phar.1924
|View full text |Cite
|
Sign up to set email alerts
|

Fosfomycin for the Treatment of Cystitis in the Abdominal Solid Organ Transplant Population

Abstract: FOS appears to be successful in the treatment of cystitis in aSOT recipients. Multidose therapy did not significantly improve success over a single-dose regimen. Further prospective studies are needed to elucidate the true efficacy of FOS in the aSOT population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
(46 reference statements)
0
3
1
Order By: Relevance
“…9 There is also minimal literature supporting the use of FOS in the SOT population. 4,[6][7][8]14 The studies that are available delineate treatment success in the setting of MDR pathogens but do not specifically address success in those patients with renal impairment. This analysis suggests that, overall, the use of FOS for treatment of cystitis in the SOT population appears to be successful, with cure rates >85%.…”
Section: Discussionmentioning
confidence: 99%
“…9 There is also minimal literature supporting the use of FOS in the SOT population. 4,[6][7][8]14 The studies that are available delineate treatment success in the setting of MDR pathogens but do not specifically address success in those patients with renal impairment. This analysis suggests that, overall, the use of FOS for treatment of cystitis in the SOT population appears to be successful, with cure rates >85%.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that fosfomycin may play a role in the treatment of MDR bacteria including MDR Pseudomonas aeruginosa , extended‐spectrum β‐lactamase (ESBL)–producing Enterobacteriaceae , carbapenem‐resistant Klebsiella pneumoniae , vancomycin‐resistant Enterococcus faecium (VRE), and methicillin‐resistant Staphylococcus aureus . Nevertheless, and despite the above‐mentioned advantages, available experience on the usefulness and safety of oral fosfomycin for the treatment of symptomatic UTI (mainly in the form of cystitis) or asymptomatic bacteriuria (AB) among KTRs are based on single‐center series with a small number of cases and poor representation of MDR strains. Thus the aim of the study was to assess the efficacy and safety of oral fosfomycin for the treatment of lower UTI in a large contemporary multicenter cohort of KTRs in Spain.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies found comparable clinical cure rates. [66][67][68] A more recent study found clinical and microbiological cure rates of 84% (120/143)) and 70% (59/84), respectively, although in these studies FT was used as first-line treatment (83.2%) instead of as salvage treatment in our study (66.0%) and for a longer duration (median 7 days vs. 1 day in our study). 69 Also within each study, variations in treatment duration and interval were large.…”
Section: Definitions Manifestations and Classificationscontrasting
confidence: 62%
“…[55][56][57] Structural problems in some countries, but sporadic challenges in the Netherlands, are the high incidence of colistin resistant Enterobacterales, further . 7,65,66 In some European countries, prevalence of CRE among K.pneumoniae is up to 60%, while this is only 0.2% in the Netherlands. 7,67 Some populations require frequent use of broad-spectrum antimicrobials, which facilitates selection of antibiotic-resistant bacteria and diminishes the arsenal of antibiotic options for UTI.…”
Section: Definitions Manifestations and Classificationsmentioning
confidence: 99%